The lip gene contributes to the virulence of Aeromonas veronii strain TH0426. (June 2022) - Wang, Hong; Lin-Zhao, Ze; Jie-An, Ding; Lin-Wang, Jing; Tong-Yang, Bin; Huan-Kang, Yuan; Xing-Zhang, Dong; Chao-Song, Hai; Feng-Shan, Xiao; Dong-Qian, Ai
Abstract: Aeromonas veronii ( A. veronii ) is a pathogen that can infect aquatic organisms and mammals and has caused irrecoverable economic losses to the aquaculture industry. The results of an epidemiological investigation showed that the number of cases of A. veronii have increased gradually in recent years, and its drug resistance and virulence has shown an upward trend. In this study, we constructed an A. veronii mutant strain Δ lip, by homologous recombination and studied its function. The results showed that there was no significant difference in the biofilm formation ability between the Δ lip and the wild-type strain, but the toxicity of the Δ lip to EPC cells and its ability to adhere to EPC cells were significantly reduced. The LD50 value of the Δ lip to zebrafish was 7.40-fold higher than that of the wild-type strain. In addition, after 24 h and 72 h, the bacterial loads of the Δ lip in the organs of crucian carp were significantly lower than those in the wild-type strain. In conclusion, the mutant strain Δ lip led to a decrease in the adhesion and virulence of the wild-type strain, which lays a foundation to further understand lip gene function and the pathogenic mechanism of A. veronii . Highlights: The adhesion ability of A. veronii to EPCs and its pathogenicity to zebrafish was significantly weakened by the deletion of the lip gene. Preliminary clarification of the lip gene function in A. veronii can further lay the foundation for revealing the complex pathogenic mechanism of A. veronii.